2018
DOI: 10.1136/bmjopen-2018-023569
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of primary care before a childhood cancer diagnosis: do socioeconomic factors matter?: A Danish nationwide population-based matched cohort study

Abstract: ObjectivesEarly diagnosis of childhood cancer is critical. Nevertheless, little is known about the potential role of inequality. This study aims to describe the use of primary care 2 years before a childhood cancer diagnosis and to investigate whether socioeconomic factors influence the use of consultations and diagnostic tests in primary care.DesignA national population-based matched cohort study.Setting and participantsThis study uses observational data from four Danish nationwide registers. All children age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…This may seem counter-intuitive given their more advanced disease at diagnosis and lower survival. However, it is consistent with other data from the UK [ 39 , 40 ], Denmark [ 41 ] and Australia [ 42 ], as well as with an ecological study of healthcare trusts in England which showed symptom awareness for breast cancer was similar across the socio-economic spectrum, although help-seeking behaviours were slightly lower in more deprived areas [ 43 ]. Breast cancer is characterised by especially short pre-diagnosis presentation intervals [ 44 ] which may suggest that the lack of association observed here between peri-diagnostic factors and survival is unique to this malignancy.…”
Section: Discussionsupporting
confidence: 90%
“…This may seem counter-intuitive given their more advanced disease at diagnosis and lower survival. However, it is consistent with other data from the UK [ 39 , 40 ], Denmark [ 41 ] and Australia [ 42 ], as well as with an ecological study of healthcare trusts in England which showed symptom awareness for breast cancer was similar across the socio-economic spectrum, although help-seeking behaviours were slightly lower in more deprived areas [ 43 ]. Breast cancer is characterised by especially short pre-diagnosis presentation intervals [ 44 ] which may suggest that the lack of association observed here between peri-diagnostic factors and survival is unique to this malignancy.…”
Section: Discussionsupporting
confidence: 90%
“…Delay has been raised as a possible explanation for social inequality in utilization of primary care [ 14 ] and survival among children with cancer, also within the Danish welfare state [ 46 ]. We are aware, the study design does not allow any conclusions about the influence of socioeconomic position [ 47 ] on events or outcomes along the cancer trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…There is only limited research available about barriers to early diagnosis of childhood cancer and most of this research uses quantitative methods. Studies on diagnostic delay have examined predictors and medical systems [2,10,[14][15][16][17], showing how differences in HCS may account for variation in TTD [18][19][20][21]. Studies of parents' experiences and accounts of the pathway to diagnosis have also been conducted showing that, given the rarity of childhood cancer, parents do not immediately interpret their children's symptoms in the context of cancer, and many symptoms are initially managed without consulting a general practitioner (GP) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation and/or reorganization of services may lead to socioeconomic differences in uptake. This has i.e., been observed for uptake and completion of the newly introduced HPV vaccination program in Danish adolescent girls [2]. Although knowledge about socioeconomic inequality in the provision of community-based rehabilitation for people with cancer is limited, recently published evidence points to social inequality in referral to rehabilitation [13,14].…”
Section: Introductionmentioning
confidence: 92%
“…Even though the health care system ensures tax-funded and equal access to health care, there is a marked social inequality in cancer prognosis in Denmark. This is documented at all levels from the GP [1,2] to the highly specialized multidisciplinary in-hospital cancer treatments (i.e., [3,4]). The social differences in prognosis are not trivial.…”
Section: Introductionmentioning
confidence: 99%